Die Klimageschichte der hohen nördlichen Breiten seit dem mittleren Miozän: Hinweise aus sedimentologischtonmineralogischen Analysen (ODP Leg 151, zentrale Framstraße) - Winkler, Amelie (1998)
This study presents the results of high-resolution sedimentological and clay mineralogical investigations on sediments from ODP Sites 908A and 909A/C located in the central Fram Strait. The objective was to reconstruct the paleo-climate and paleo-oceanography of the high northern latitudes since the middle Miocene. The sediments are characterised in particular by a distinctive input of ice-rafted material, which most probably occurs since 6 Ma and very likely since 15 Ma. A change in the source area at 11.2 Ma is clearly marked by variations within clay rnineral composition and increasing accumulation rates. This is interpreted as a result of an increase in water mass exchange through the Fram Strait. A further period of increasing exchange between 4-3 Ma is identified by granulometric investigations and points to a synchronous intensification of deep water production in the North Atlantic during this time interval. A comparison of the components of coarse and clay fraction clearly shows that both are not delivered by the same transport process. The input of the clay fraction can be related to transport mechanisms through sea ice and glaciers and very likely also through oceanic currents. A reconstruction of source areas for clay minerals is possible only with some restrictions. High smectite contents in middle and late Miocene sediments indicate a background signal produced by soil forrnation together with sediment input, possibly originating from the GreenlandScotland Ridge. The applicability of clay mineral distribution as a climate proxy for the high northern latitudes can be confirrned. Based on a comparison of sedirnents from Site 909C, characterised by the smectite/illite and chlorite ratio, with regional and global clirnatic records (oxygen isotopes), a middle Miocene cooling phase between 14.8-14.6 Ma can be proposed. A further cooling phase between 10-9 Ma clearly shows similarities in its progress toward drastic decrease in carbonate sedimentation and preservation in the eastern equatorial Pacific. ...